2018
DOI: 10.1017/s1751731117001707
|View full text |Cite
|
Sign up to set email alerts
|

Blood profile and meat quality of Holstein-Friesian steers finished on total mixed ration or flaxseed oil-supplemented pellet mixed with reed canary grass haylage

Abstract: Holstein-Friesian steer beef production is renowned globally as a secondary product of the milk industry. Grass feeding is a common practice in raising Holstein steers because of its low cost. Furthermore, grass feeding is an alternative way to produce beef with a balanced n-6 to n-3 fatty acids (FAs) ratio. However, the performance and meat quality of Holstein-Friesian cattle is more likely to depend on a high-quality diet. The aim of this study was to observe whether feeding two mixed diets; a corn-based tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Ruminant milk and meat might contain more SFA because of the biohydrogenation occurring in the rumen. There are considerable studies focusing on reducing the biohydrogenation by adding more unsaturated fatty acids of feedstuff [32,33], protecting unsaturated fatty acids [34] or supplying feedstuff against biohydrogenation [35] in ruminants' diets. In the present study, PUFA were significantly higher in 10% and 15% groups than that in control group or 5% group (p<0.05), and it might due to the antimicrobial activities in the diet supplemented with B. papyrifera silage, as it is reported that prenylated flavonoids isolated from B. papyrifera have antimicrobial activity [36,37] which might affect the rumen microorganism by reducing the biohydrogenation of fatty acids in the rumen, and also dietary antioxidant activity might increase PUFA content in meat [38,39].…”
Section: Amino Acids and Fatty Acids Composition In Meatmentioning
confidence: 99%
“…Ruminant milk and meat might contain more SFA because of the biohydrogenation occurring in the rumen. There are considerable studies focusing on reducing the biohydrogenation by adding more unsaturated fatty acids of feedstuff [32,33], protecting unsaturated fatty acids [34] or supplying feedstuff against biohydrogenation [35] in ruminants' diets. In the present study, PUFA were significantly higher in 10% and 15% groups than that in control group or 5% group (p<0.05), and it might due to the antimicrobial activities in the diet supplemented with B. papyrifera silage, as it is reported that prenylated flavonoids isolated from B. papyrifera have antimicrobial activity [36,37] which might affect the rumen microorganism by reducing the biohydrogenation of fatty acids in the rumen, and also dietary antioxidant activity might increase PUFA content in meat [38,39].…”
Section: Amino Acids and Fatty Acids Composition In Meatmentioning
confidence: 99%
“…However, accomplishing this enrichment in ruminants is challenging owing to the biohydrogenation of fatty acids, which occurs in the rumen (Bessa et al, 2000;Lunn & Theobald, 2006). In the last decade several attempts have been made to increase the PUFA content in meat from ruminant livestock, including dietary supplementation with linseed and linseed oil in lambs (Giannico et al, 2009;Colonna et al, 2011;Toteda et al, 2011;Facciolongo et al, 2018), in kids (Rotondi et al, 2018), and in steers (Juárez et al, 2012;Ragni et al, 2014;Utama et al, 2018). Heat extrusion of oil from linseed has been shown to be a successful way of protecting the seeds from ruminal degradation (Mustafa et al, 2003;Gonthier et al, 2004;Raes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Total mixed ration (TMR) provides forage and simultaneously increased the digestibility of nutrients and digestible energy content (12). It has several advantages, providing homogeneous feed to animals over time, reducing feed costs, and saving time (13). However, intensive fattening is better than other farming systems, regardless of age and sex (14).…”
Section: Introductionmentioning
confidence: 99%